Burnout effects on cellular ceramics obtained from gelatine gelcasted emulsified suspensions. Issue 3 (March 2015) - Freitas, C.; Vitorino, N.; Abrantes, J.C.C.; Frade, J.R.
Abstract: Differential thermal analysis, thermogravimetry and dilatometry were used to study burnout changes occurring during the earliest stages of firing of cellular ceramics obtained by gelcasting of emulsified suspensions. These analyses provide information on microstructural rearrangements during the initial burnout stages, and for the effects of heating rate, isothermal plateau and corresponding time on cell size distributions, average cell size and other microstructural features of resulting cellular ceramics. Compressive strength and its scattering were also related to those microstructural changes induced by burnout conditions.